An Open Cranial Vault Remodeling Procedure for Craniosynostosis: A Retrospective Study - GUNDAG, MELİHA; Abdallah A.; GUNDAG M.; Baloglu G. (My University, 2022)
Craniosynostosis is a skull malformation occurring due to the premature fusion of one or more cranial sutures. This pathological entity is a relatively commonly observed congenital malformation and is reportedly seen in 1/1,700-1,900 live births. The study aimed to evaluate the surgical outcomes of the open cranial vault remodeling (OCVR) in children with craniosynostosis. Medical records of 76 children with craniosynostosis who were diagnosed at the neurosurgery departments of our centers for 11 years (from January 2010 to December 2020) were retrospectively examined. Among them, 54 consecutive children who underwent OCVR were included in this study. Surgical outcomes were discussed with a related literature review. Fifty-four (32 males and 22 females) consecutive children received OCVR for craniosynostosis with a mean age of 12.6 & PLUSMN; 7.1 months. Eight children were syndromic. Three children were shunt-induced craniosynostosis. Syndromic children were four with Apert, two with Pfeiffer, and two with Crouzon syndrome. Twelve children were brothers/sisters. The misshapen skull was the most commonly recorded symptom in 49 children (90.7%). The most affected sutures were bicoronal craniosynostosis found in 20 children. The complication rate was 9.3% ( n = 5). Two of these five children needed reoperation for optimal remodeling. One child died postoperatively in the intensive care unit due to cardiac arrest. These findings demonstrated that the OCVR approach is an efficient surgical method to get good outcomes. Satisfactory results with an acceptable complication rate can be obtained with expert hands. Further studies are warranted to support these findings.
Keywords: craniosynostosis; open cranial vault remodeling; cranioplasty; children; surgical outcomes